Analysis of presumed IQOS influencer marketing on Instagram in the Czech Republic in 2018–2019 - Hejlová, Denisa; Schneiderová, Soňa; Klabíková Rábová, Tereza; Kulhánek, Adam (Adiktologie, 2019)
BACKGROUND: Heated tobacco products (HTP) are novel electronic devices that produce an aerosol by heating modified tobacco. In July 2017, Philip Morris launched a heated tobacco product, IQOS, on the Czech market. The release of IQOS was promoted by a massive marketing campaign using various marketing channels. AIM: This paper presents an analysis of the influencers' posts promoting a heated tobacco product (HTP), IQOS, produced by Philip Morris, in the Czech Republic. METHODS: Critical discourse analysis (CDA) was used to uncover the hidden power relationships in both textual and visual representations of IQOS in Instagram posts. We analysed the posts of 22 Czech influencers identified with the hashtags #IQOSambassador, #IQOSambasabor, #IQOSlounge, #IQOSveVarech, and #mujIQOS, together with associated pictures and videos on Instagram. RESULTS: The hashtag #iqosambassador was used internationally in 940 posts (as of May 16, 2019). Our findings show subtle forms of persuasion that associate the IQOS product with an aspirational, exclusive lifestyle, healthy living, and a relaxed atmosphere within a community of friends. Preliminary results also show that influencers promoted IQOS to any and all Instagram users (including children and non-smokers). Covert advertising was indicated indirectly by the use of hashtags (#notriskfree, #onlyforadults, and #iqosambassador), which might be evidence that the influencers were paid indirectly by a digital marketing or PR agency. CONCLUSIONS: Czech celebrities and influencers have been actively presenting IQOS in their posts and videos since 2018 on Instagram. They present IQOS as a gateway to an aspirational, healthy, attractive and celebrity lifestyle. The preliminary results are being published as a part of a larger interdisciplinary research project by Charles University, Prague.